2015
DOI: 10.18869/acadpub.3dj.4.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatized Articular Tubercle and Pneumatized Roof of Glenoid Fossa on Cone Beam Computed Tomography: Prevalence and Characteristics in Selected Iranian Population

Abstract: Mastoid pneumatization is often complete by the age of 5-years and may involve the temporo-mandibular joint (TMJ) region, including the pneumatized articular tubercle (PAT) and pneumatized roof of the glenoid fossa (PRGF). To prevent surgical complications, the diagnosis of these air cells is important. The aim of this study was to determine the prevalence and characteristics of PAT and PRGF in the Iranian population. Materials and methods: In this cross-sectional study, convenience sampling was used to select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In contrast most of the studies using the cone beam computed tomography (CBCT) have reported higher prevalence rates. [20,21,25,26] however only one study by Ribeiro-Nascimento et al (2015) using CBCT has reported lower prevalence rate of 3.3%. [3] Prevalence rate as high as 68.5% also have been reported in studies conducted using CBCT.…”
Section: Prevalence Of Zygomatic Air Cell Defectmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast most of the studies using the cone beam computed tomography (CBCT) have reported higher prevalence rates. [20,21,25,26] however only one study by Ribeiro-Nascimento et al (2015) using CBCT has reported lower prevalence rate of 3.3%. [3] Prevalence rate as high as 68.5% also have been reported in studies conducted using CBCT.…”
Section: Prevalence Of Zygomatic Air Cell Defectmentioning
confidence: 99%
“…Studies involving zygomatic air cell defect have been conducted using different imaging modalities over the years also taking into consideration occurrence (unilateral/bilateral) and gender distribution. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (Table1)…”
Section: Studies Involving Zygomatic Air Cell Defectmentioning
confidence: 99%
See 3 more Smart Citations